Effects of source and level of added chromium on growth performance of starter pigs - O'Quinn, P.R.; Musser, R.E.; Owen, K.Q.; Blum, S.A.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 35-d growth trial was conducted with conventionally weaned nursery pigs to evaluate the efficacy of supplemental chromium (Cr) as either chromium nieotinate (CrNic) or chromium picolinate (CrPic). Neither source nor level of supplemental Cr had any effect on weanling pig growth performance or immune status. Equal levels of CrNic and CrPic produced similar results, except that pigs fed CrPic had higher serum Cr concentrations than pigs fed CrNic. These data suggest no beneficial responses to supplemental CrNic or CrPic in nursery pig diets.
Keywords: Swine; Starter pigs; Chromium; Chromium Nicotinate; Growth performance